2012
DOI: 10.1038/ng.2331
|View full text |Cite
|
Sign up to set email alerts
|

De novo germline and postzygotic mutations in AKT3, PIK3R2 and PIK3CA cause a spectrum of related megalencephaly syndromes

Abstract: Megalencephaly-capillary malformation (MCAP) and megalencephaly-polymicrogyria-polydactyly-hydrocephalus (MPPH) syndromes are sporadic overgrowth disorders associated with markedly enlarged brain size and other recognizable features1-5. We performed exome sequencing in three families with MCAP or MPPH and confirmed our initial observations in exomes from 7 MCAP and 174 control individuals, as well as in 40 additional megalencephaly subjects using a combination of Sanger sequencing, restriction-enzyme assays, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
661
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 639 publications
(708 citation statements)
references
References 54 publications
(65 reference statements)
33
661
2
1
Order By: Relevance
“…Although they both cause hamartomas and several other characteristics, individuals carrying the Cowden syndrome are also prone to elevated cancer risk, in particular cancers of the thyroid and breast. 144 While germline mutations in PIK3CA and AKT3 (the Akt isoform expressed in neural tissue) may cause megalencephaly, 145 a most recent study 146 reported PI3KCA, but also AKT1 germline mutations in some families revealing the Cowden or a Cowden-like syndrome. Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…Although they both cause hamartomas and several other characteristics, individuals carrying the Cowden syndrome are also prone to elevated cancer risk, in particular cancers of the thyroid and breast. 144 While germline mutations in PIK3CA and AKT3 (the Akt isoform expressed in neural tissue) may cause megalencephaly, 145 a most recent study 146 reported PI3KCA, but also AKT1 germline mutations in some families revealing the Cowden or a Cowden-like syndrome. Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…10 Although we did not observe any significant change in the expression level of TSC2 or mTORC1 in skin fibroblast of the patient (Figure 2b), we cannot discard that the involvement of HERC1 in the mTOR pathway could be tissue-specific. Given that the megalencephaly phenotype is largely attributed to misregulation of the mTOR pathway, [3][4][5] it is likely that loss of HERC1 could impair this pathway early in brain development. Loss of HERC1 protein may also affect intracellular membrane trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…2 De novo mutations in PIK3CA, AKT3 and MTOR are found in 30% of cases of hemimegalencephaly, 3 whereas de novo and postzygotic mutations in AKT3, PIK3R2, PIK3CA and CCND2 cause 74% of cases of megalencephaly-capillary malformation and megalencephaly-polymicrogyria-polydactyly-hydrocephalus. 4,5 Moreover, mutations in other components of mTOR could manifest neurological symptoms without megalencephaly, such as ID, autism or epilepsy, as seen in patients with mutations in TSC1 (tuberous sclerosis complex 2), TSC2, PINK1 and DISC1. 6 These findings strongly support the role of the mTOR pathway in the development and function of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Es handelt sich somit in der Regel um Mutationen, die postzygotisch während der Embryonalentwicklung auftreten (Übersicht zu Mosaiken unter Kurth und Grimm [22]). Daher wird in diesen Fällen auch von postzygotischen Mutationen/Mosaiken gesprochen [36]. Mutationsmosaike werden zunehmend häufiger als Ursache genetisch bedingter Krankheitsbilder erkannt, was neben der größeren klinischen Aufmerksamkeit vor allem an empfindlicheren Nachweismethoden liegt.…”
Section: Somatische Mutationsmosaikeunclassified